High-Throughput Microfluidic 3D Cytotoxicity Assay for Cancer Immunotherapy (CACI-IMPACT Platform) - Park, Dohyun; Son, Kyungmin; Hwang, Yunchan; Ko, Jihoon; Lee, Younggyun; Doh, Junsang; Jeon, Noo Li (Frontiers in Immunology, 2019)
Adoptive cell transfer against solid tumors faces challenges to overcome tumor microenvironment (TME), which plays as a physical barrier and provides immuno-suppressive conditions. Classical cytotoxicity assays are widely used to measure killing ability of the engineered cytotoxic lymphocytes as therapeutics, but the results cannot represent the performance in clinical application due to the absence of the TME. This paper describes a 3D Cytotoxicity Assay for Cancer Immunotherapy using an Injection Molded Plastic Array CulTure (CACI-IMPACT) device for assessing killing abilities of cytotoxic lymphocytes in 3D microenvironment through a spatiotemporal analysis of the lymphocytes and cancer cells embedded in 3D extra cellular matrix (ECM). Rail-based microfluidic design was integrated within a single 96-well and the wells were rectangularly arrayed in 2 x 6 to enhance the experimental throughput. The rail-based microstructures facilitate hydrogel patterning with simple pipetting so that hydrogel pre-solution aspirated with a 10 μl pipette can be patterned in 10 wells within 30 seconds. To demonstrate 3D cytotoxicity assay, we patterned HeLa cells encapsulated by collagen gel and observed infiltration, migration and cytotoxic activity of NK-92 cells against HeLa cells in the collagen matrix. We found that 3D ECM significantly reduced migration of cytotoxic lymphocytes and access to cancer cells, resulting in lower cytotoxicity compared with 2D assays. In dense ECM, the physical barrier function of the 3D matrix was enhanced, but the cytotoxic lymphocytes effectively killed cancer cells once they contacted cancer cells. The results implied ECM significantly influences migration and cytotoxicity of cytotoxic lymphocytes. Hence, the CACI-IMPACT platform, enabling high-throughput 3D co-culture of cytotoxic lymphocyte with cancer cells, has the potential to be used for pre-clinical evaluation of cytotoxic lymphocytes engineered for immunotherapy against solid tumors.